Best evidence summary for preventing and preventing epidermal growth factor receptor inhibitors induced paronychia in cancer patients - Li, Kexuan; Qiu, Xiuyue; Zhang, Jiayu; Zhou, Yingshuyi; Fan, Youfen (Frontiers in Oncology, 2025)
ObjectiveTo evaluate and summarize the best evidence for preventing and managing epidermal growth factor receptor inhibitors induced paronychia in cancer patients. It aims to provide a reference for medical staff.MethodsWe systematically searched for evidence on paronychia symptoms in 14 databases such as Cnki、Wanfang, 7 guide websites such as GIN and NZGG, and 8 professional websites such as UICC and ACS from database establishment to August 2024. Two researchers evaluated the quality of the literature and extracted the data.ResultsA total of 20 articles were included in this study, including 5 clinical decisions、5 guidelines、3 evidence summaries 、3 recommended practices, and 4 experts consensuses. Finally, 12 pieces of evidence were summarized from 4 aspects, including risk factor assessment, professional healthcare training, preventive measures, and therapeutic measures.ConclusionOur research summarizes the best evidence for preventing and managing epidermal growth factor receptor inhibitors induced by paronychia in cancer patients. In the actual clinical application, it is necessary to fully consider the clinical situation, combine the judgment of professionals and patients’ wishes, follow the principle of individualization, analyze the obstacles and facilitating factors of the application of evidence, and apply the evidence to the clinical practice prudently.